Replanteamineto de un modelo de negocios basado en la productividad aplicado a las pymes de brokers de seguros tomando como referencia la Empresa Fielseg S.A. - Lincango Simbaña, Bélgica Janeth (2015)
Fielseg S.A. It is a company dedicated to consulting and production of secure mass with eight years of experience in the market. Its main customers are shaped by all types of companies who are granted life insurance, Medical Assistance Personal Accident. During 2013 the company introduced financial problems due to the floor of a very important customer, which generated more than 40% of revenues. A root of this problem could be detected a number of drawbacks in the development and growth of the company, lack of qualified personnel, especially the commercial area hindered growth and customer acquisition additionally not had a marketing plan that is, I was not focused on productivity growth and innovation to guide the company to achieve its objectives. We must take into account that poor collection management made the loan recovery less efficient. Taking into account all these deficiencies, corrective action was taken for the company to achieve higher growth and position in the insurance market through innovation in business processes, giving the customer a different service with high technological approach digital. With these actions, the company aims to achieve a focus on quality, innovation, production efficiency, sustainability and social inclusion, achieving a representative growth over the next year and their financial situation - economically more sustainable